A Single Nonsynonymous Substitution in the RNA-Dependent RNA Polymerase of Potato virus Y Allows the Simultaneous Breakdown of Two Different Forms of Antiviral Resistance in Capsicum annuum - Benoît Moury; Thierry Michon; Vincent Simon; Alain Palloix (Viruses, 2023)
The dominant Pvr4 gene in pepper (Capsicum annuum) confers resistance to members of six potyvirus species, all of which belong to the Potato virus Y (PVY) phylogenetic group. The corresponding avirulence factor in the PVY genome is the NIb cistron (i.e., RNA-dependent RNA polymerase). Here, we describe a new source of potyvirus resistance in the Guatemalan accession C. annuum cv. PM949. PM949 is resistant to members of at least three potyvirus species, a subset of those controlled by Pvr4. The F1 progeny between PM949 and the susceptible cultivar Yolo Wonder was susceptible to PVY, indicating that the resistance is recessive. The segregation ratio between resistant and susceptible plants observed in the F2 progeny matched preferably with resistance being determined by two unlinked recessive genes independently conferring resistance to PVY. Inoculations by grafting resulted in the selection of PVY mutants breaking PM949 resistance and, less efficiently, Pvr4–mediated resistance. The codon substitution E472K in the NIb cistron of PVY, which was shown previously to be sufficient to break Pvr4 resistance, was also sufficient to break PM949 resistance, a rare example of cross-pathogenicity effect. In contrast, the other selected NIb mutants showed specific infectivity in PM949 or Pvr4 plants. Comparison of Pvr4 and PM949 resistance, which share the same target in PVY, provides interesting insights into the determinants of resistance durability.